High intensity focused ultrasound serves as a salvage treatment for uterine arteriovenous fistula when uterine artery embolization fails and pregnancy outcomes: a case report and literature review - Shanyu Huang; Mingzhu Ye; Xiaoxiao Xi; Waixing Li; Xiaogang Zhu; Xin Sun (International Journal of Hyperthermia, 2025)
Uterine arteriovenous fistula (UAVF) is an abnormal connection formed between the branches of the uterine artery and the venous plexus, accounting for 1%–2% of all reproductive system and abdominal bleeding. In recent years, the incidence has been gradually increasing due to acquired causes such as uterine surgery and pregnancy. The common clinical symptom is painless and irregular vaginal bleeding, which can lead to hemorrhagic shock. There is no standardized and unified treatment for UAVF. At present, uterine artery embolization (UAE) is considered the first-choice treatment for UAVF in clinical practice, but it is prone to treatment failure due to various potential complications. HIFU, as a noninvasive treatment, is currently used in a limited number of cases for the treatment of UAVF, and a few literature reports have shown clinical effects after high-intensity focused ultrasound (HIFU) treatment. This paper reports a case that HIFU was successfully used to treat UAVF after the failure of UAE, and the patient successfully became pregnant, indicating that HIFU can be used as an alternative after the failure of UAE treatment for UAVF, without affecting subsequent pregnancy.